Covid-19 Crisis Fuels Hostility against Foreigners - Vojtech Bartos; Michal Bauer; Jana Cahlikova; Julie Chytilová (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Aggressive behavior against out-group members often rises during periods of economic hardship and health pandemics. Here we test the widespread concern that the Covid-19 crisis may fuel hostility against people from other nations or ethnic minorities. Using a controlled money-burning task, we elicited hostile behavior among a nationally representative sample (n=2,186) in the Czech Republic, at a time when the entire population was under lockdown. We provide causal evidence that exogenously elevating salience of Covid-related thoughts magnifies hostility against foreigners – people living in the EU, the USA and especially Asia. This behavioral response is large in magnitude and holds across various demographic sub-groups. At the same time, we find virtually no effects on behavior towards domestic out-groups, including minorities and migrants. The results underscore the importance of not inflaming anti-foreigner sentiments and suggest that efforts to restore international trade and cooperation will need to address both social and economic damage.
Keywords: C90; D01; D63; D91; J15; 330; COVID-19 pandemic; scapegoating; hostility; inter-group conflict; discrimination; experiment